The "self-disclosure" and "self-presentation" views of item response dynamics and personality scale validity - Johnson, John A. (1981)
Investigated whether objective self-report measures of personality are better regarded as sources of factual information about the self (i.e., as self-disclosures) or as ways to instruct others about how one is to be regarded (i.e., as self-presentations). The 2 perspectives were compared by testing the unique, divergent predictions each perspective made about the kinds of personality variables associated with consistency in self-description. The battery of tests included the California Psychological Inventory and Adjective Check List. For 3 groups of Ss (155 normal adults, 69 murderers, and 47 undergraduates) almost all of the "self-presentation variables" were correlated significantly with consistency, whereas none of the "self-disclosure variables" was correlated with the criterion.
Includes bibliographical references.
DOI: 10.1037/0022-3514.40.4.761
Keywords: Self-disclosure.; Self-presentation.